REGISTERED OUTBREAKS OF ACUTE VIRAL HEPATITIS A IN STARA ZAGORA REGION, FOR THE PERIOD SEPTEMBER 2019 – MARCH 2020, IN THE MUNICIPALITIES BR. DASKALOVI, HRISHTENI, GALABOVO IN BULGARIA - I. Simeonova; T. Perchemlieva; St. Petrova; G. Trifonov; G. Iliev3 , I. Mladenova (Trakia Journal of Sciences)
Viral hepatitis type A is an acute infectious disease, occupying 75% of all viral hepatitis. Purpose of the study was to investigate three outbreaks, of viral hepatitis A in the municipalities of Stara Zagora region, from 09.2019-03.2020 in schools and kindergartens. Methods: We investigated all cases from viral hepatitis A, for the municipalities of Bratya Daskalovi26, Hrishteni-19, Galabovo-21. A retrospective analysis and descriptive epidemiological methods have been used. Results: The gender distribution shows that men were affected in 56% and women in 44%. The children in the age group of 5-9 years - 49%, as well as of 1 - 4 years - 19.7% are most ill. The peak in the development of the outbreaks is in December 2019 (18%) and January 2020 (48%), which lasts until March with the so-called "Epidemic tail". Contact persons were not covered by the hepatitis A vaccine. The faecal-oral mode of transmission of infection has been proven. Specialized companies were engaged for the activities of current and final disinfection. Health educational activities aimed at improving hygiene habits have been carried out. Conclusion: To prevent the outbreaks the cases have to be timely reported; Early examination of contact persons; Applications of a vaccine on the contact persons.